Characterization and Properties Investigation on the Industrial Mold finishing stone - MOHAMMAD ALSAAFEEN, MOUAATH (IRC, 2017)
Mold finishing stone is made of aluminum oxide or alumina and it’s used as a cutting tool and it’s generally used as a cutting tool for metals. The resistance of the alumina against the outside impacts is good. Mold finishing stone is used in the Electrical discharge machining (EDM), surface finishing process after the EDM processes, deep grooves and edges processes. The brittleness of the ceramic cutting tools makes it less reliable and that leads to failure. This project intends to investigate the properties of the samples available of the industrial mold finishing stone to validate the industrial standard. The research plan is to apply experimentation on three specimens of mold finishing stone from the manufacturing company, the cutting tools samples are labeled as good, acceptable and bad according to their properties. Several experiments are chosen to be conducted according to the methodology of the project and those are, Flexural Strength test followed by Optical microscope and Scanning electron microscope (SEM) to be able to differentiate between the specimens microstructure the compare and validate the result with the company standard. The SEM images will be taken on 100x, 500x and 1000x magnifications, however the flexural strength testing will be following the ASTM C 1161 – 02c standard. The microscope images and the SEM images supported the company standard since the level of porosity of the three specimens differs, specimen A (Good) had the lowest level followed by specimen B (acceptable) and lastly specimen C (Bad). The flexural strength testing showed that specimen A have the highest flexural strength with the value of 21.69 MPa followed by specimen B with the value of 16.97 MPa then specimen C that had the lowest value which was 15.24 MPa. The results of the experimentations validated the industrial standard for the mold finishing stone cutting tool